2012
DOI: 10.1371/journal.pone.0040678
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin in Ovarian Cancer: Foe In Vitro and Friend In Vivo?

Abstract: Stromal elements within a tumor interact with cancer cells to create a microenvironment that supports tumor growth and survival. Adrenomedullin (ADM) is an autocrine/paracrine factor produced by both stromal cells and cancer cells to create such a microenvironment. During differentiation of macrophages, ADM is produced in response to pro-inflammatory stimuli and hypoxia. In this study we investigated the role of ADM as a growth factor for ovarian cancer cells and as a modulator of macrophages. We also analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…However, a recent study reported the opposite, namely that high expression level of ADM in primary tumors was related to a better outcome. They also observed that, for the vasoactive properties, actually the peptide could increase perfusion and chemotherapy sensitivity [22]. The inconsistency might be attributed to the differences within the study populations and/or designs, which makes the precise function of ADM in this disease more complicated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study reported the opposite, namely that high expression level of ADM in primary tumors was related to a better outcome. They also observed that, for the vasoactive properties, actually the peptide could increase perfusion and chemotherapy sensitivity [22]. The inconsistency might be attributed to the differences within the study populations and/or designs, which makes the precise function of ADM in this disease more complicated.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, Baranello C. et al . noticed in vitro the capability of ADM to stimulate M2 differentiation [22]. We therefore considered that ADM, derived from ovarian cancer cells, might be a novel target to inhibit macrophages polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour cell lines evaluated included small cell lung carcinomas, non-small cell lung carcinomas, breast, nervous system (glioblastoma, neuroblastomas), ovarian, prostate, adrenal, chondrosarcoma, and chronic monocytic leukemia [ 166 ]. These data have been replicated on different tumour cell lines such as pancreatic cell lines (PANC1, L3.6, HPAFII, SU86.86) [ 110 , 116 , 169 ], gliomas [ 170 , 171 ], prostate cancer cell lines [ 162 , 172 175 ], ovarian cancer [ 149 , 176 , 177 ], osteosarcoma [ 109 ], renal carcinoma [ 121 , 178 ], multiple myeloma [ 179 ], bladder urothelial cell carcinoma [ 120 ], pituitary adenomas [ 145 ], colorectal cancer [ 119 , 147 , 148 ], breast cancer [ 144 ], endometrial cancer [ 38 ], hepatocellular carcinoma [ 132 ] and others.…”
Section: Introductionmentioning
confidence: 87%
“…AM gene expression levels may play a key role in the biology of epithelial ovarian cancer and may define a more aggressive tumour phenotype [ 124 ]. However, recent studies performed in ovarian cancer patients by Baranello et al found high expression levels of AM as a positive prognostic factor [ 149 ]. In hepatocellular carcinoma, AM expression was positively correlated with invasion and progression [ 132 , 133 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation